Implementation of a System for Protecting a Computational Algorithm Using a Local Network of Personal Computers - Kostromitin, K. I.; Dokuchaev, B. N.; Kozlov, D. A. (2021 International Russian Automation Conference (RusAutoCon), 2021)
An applied problem associated with the development of a comprehensive information protection system (computational algorithm) in a local computer network is to ensure information security of specific nodes of this network, information in which is of some value to their owner, due to its unknown to third parties, for example, information constituting trade secrets. In this case, a certain computational algorithm (computational function) acts as the protected information, with the help of which it is possible to perform a unique transformation of a specific input parameter, or data set, into an output value - the final result of the algorithm. At the same time, the input and output information, as well as information circulating outside the boundaries of the algorithm, is of no value to the user of this LAN, therefore, is not subject to protection.